Análisis de la relación entre la pobreza y empleo en el departamento de Loreto, periodo 2015 - 2019 - Chavez Perez, Francesca Guadalupe (2021)
One of the most efficient ways to combat poverty is by creating jobs in the formal sector. This research aims to determine the relationship between poverty and employment in the department of Loreto, in the period 2015 - 2019. Oriented by this purpose, the present study of a Quantitative type, Correlational level and Non-Experimental design was carried out. The research concludes that poverty has not relationship or determination with employment, a conclusion supported by the statistical test that resulted in the Correlation Coefficient r = -0.402558360; and in the Correlation Coefficient R2 = 0.162053233; which demonstrates the lack of statistical association or significance between poverty and employment. The type of employment that predominates in the department of Loreto is informal employment, where 81.35% of workers are located, equivalent to 411,510 people. For its part, formal employment only employed 94,350 workers, which represents 18.65. The average real monthly per capita income had a variable behavior during the five years, reaching its maximum value in 2017 being S /. 697.00 and the lowest in 2016 with S /. 654.00. The average real monthly per capita expenditure measures the well-being of the population, and had a variable evolution throughout the five-year period, the highest value being S /. 551.00 in 2018, and the lowest S /. 517.00 of the year 2016.